Single-Phase Ternary Compounds with a Disordered Lattice and Liquid Metal Phase for High-Performance Li-Ion Battery Anodes - Li, Yanhong; Zhang, Lei; Yen, Hung‑Yu; Zhou, Yucun; Jang, Gun; Yuan, Songliu; Wang, Jeng‑Han; Xiong, Peixun; Liu, Meilin; Park, Ho Seok; Li, Wenwu (Nano-Micro Letters, 2023)
Si is considered as the promising anode materials for lithium-ion batteries (LIBs) owing to their high capacities of 4200 mAh g−1 and natural abundancy. However, severe electrode pulverization and poor electronic and Li-ionic conductivities hinder their practical applications. To resolve the afore-mentioned problems, we first demonstrate a cation-mixed disordered lattice and unique Li storage mechanism of single-phase ternary GaSiP2 compound, where the liquid metallic Ga and highly reactive P are incorporated into Si through a ball milling method. As confirmed by experimental and theoretical analyses, the introduced Ga and P enables to achieve the stronger resistance against volume variation and metallic conductivity, respectively, while the cation-mixed lattice provides the faster Li-ionic diffusion capability than those of the parent GaP and Si phases. The resulting GaSiP2 electrodes delivered the high specific capacity of 1615 mAh g−1 and high initial Coulombic efficiency of 91%, while the graphite-modified GaSiP2 (GaSiP2@C) achieved 83% of capacity retention after 900 cycles and high-rate capacity of 800 at 10,000 mA g−1. Furthermore, the LiNi0.8Co0.1Mn0.1O2//GaSiP2@C full cells achieved the high specific capacity of 1049 mAh g−1 after 100 cycles, paving a way for the rational design of high-performance LIB anode materials. Highlights: 1 Single-phase ternary GaSiP2 with a disordered lattice and liquid metal was synthesized. 2 GaSiP2 electrode achieved superior Li-storage performances in both half and full cells. 3 Unique self-healing Li-storage mechanism of GaSiP2 was analyzed.